The role of nurses in inpatient geriatric rehabilitation units: A scoping review - Nicole A. Guitar; Denise M. Connelly; Kristin Prentice; Angela Nguyen; Amanda McIntyre; Eric F. Tanlaka; Nancy Snobelen (Wiley, 2023)
Abstract Aims (1) To review and synthesize research on the contributions of nurses to rehabilitation in inpatient geriatric rehabilitation units (GRUs), and (2) to compare these reported contributions to the domains of international rehabilitation nursing competency models. The roles and contributions of nurses (e.g. Registered Practical Nurses, Registered Nurses and Licensed Practical Nurses) in GRUs are non‐specific, undervalued, undocumented and unrecognized as part of the formal Canadian rehabilitation process. Design Arksey and O'Malley's methodological framework for scoping reviews and the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Extension for Scoping Reviews guidelines were used. Methods Six databases were searched for relevant literature: MEDLINE, PsychINFO, CINAHL, EMBASE, SCOPUS and Nursing and Allied Health. English articles were included if they examined nursing roles or contributions to inpatient geriatric rehabilitation. Integrated synthesis was used to combine the qualitative and quantitative data, and thematic analysis was used for coding. Three sets of international competency models were amalgamated to explore how different nurse roles in geriatric rehabilitation were portrayed in the included literature. Results Eight studies published between 1991 and 2020 were included in the review. Five main geriatric rehabilitation nursing roles were generated from synthesis of the domains of international rehabilitation nursing competency models: conserver, supporter, interpreter, coach and advocate. Conclusions Nurses working in inpatient geriatric rehabilitation are recognized more for their role in conserving the body than their roles in supporting, interpreting, coaching and advocacy. Interprofessional team members appear to be less sure of the nurses' role in the rehabilitation unit. Nurses themselves do not acknowledge the unique rehabilitation aspects of care for older adults. Enhancing formal education, or adding continuing education courses, to facilitate role clarity for nurses in geriatric rehabilitation could improve nurses' and interprofessional healthcare team members' understandings of the possible contributions of nurses working in rehabilitation settings.